2017
DOI: 10.1007/s00284-017-1289-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of the Biocontrol Agent Bacillus amyloliquefaciens CPA-8: The Effect of Temperature, pH and Water Activity on Growth, Susceptibility to Antibiotics and Detection of Enterotoxic Genes

Abstract: This work focuses on the biological understanding of the biocontrol agent Bacillus amyloliquefaciens CPA-8 in order to accomplish the characterization required in the registration process for the development of a microorganism-based product. The tolerance of CPA-8 to grow under different pH-temperature and water activity (a )-temperature conditions was widely demonstrated. Regarding the pH results, optimum growth at the evaluated conditions was observed at 37 °C and pH between 7 and 5. On the contrary, the slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…[35][36][37] Interestingly, we found that either in protective or curative applications a higher control efficacy was achieved by BCA treatments at the lower temperature tested of 10°C. Despite the fact that B. amylolιquefaciens strains are considered to be mesophilic species showing better growth at higher temperatures, 38 our results suggest that Ba QST713 can retain its functionality at variable temperatures. Furthermore, at the lower tested temperature of 10°C, fungal spore germination and germ tube growth were delayed, allowing a longer contact of the fungus with the BCA that results in a higher control efficacy.…”
Section: Discussioncontrasting
confidence: 52%
“…[35][36][37] Interestingly, we found that either in protective or curative applications a higher control efficacy was achieved by BCA treatments at the lower temperature tested of 10°C. Despite the fact that B. amylolιquefaciens strains are considered to be mesophilic species showing better growth at higher temperatures, 38 our results suggest that Ba QST713 can retain its functionality at variable temperatures. Furthermore, at the lower tested temperature of 10°C, fungal spore germination and germ tube growth were delayed, allowing a longer contact of the fungus with the BCA that results in a higher control efficacy.…”
Section: Discussioncontrasting
confidence: 52%
“…This study demonstrated that CPA‐8 was able to maintain the same population level for 3 days under field conditions and for 45 days under postharvest storage conditions. Gotor‐Vila et al . demonstrated that CPA‐8 is a microorganism highly adapted to high temperatures under in vitro conditions, with stable viability on the stone fruit surface when exposed to 0 and 20 °C and different RH values (85, 60 and 40%) .…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Berg, compared with chemicals, microorganisms are safer, show reduced environmental damage and potentially smaller risk to human health, show much more targeted activity, are effective in small quantities, multiply themselves but are controlled by the plant as well as by the indigenous microbiota populations, decompose more quickly than conventional pesticides, reduce the development of resistance as a result of several mechanisms and can be used in conventional or integrated pest management systems. Although open to a wide range of interpretations, the data available on CPA‐89, have allowed products based on CPA‐8 to enter the last stage of their commercial development, and they are now ready for the registration process. The integration of these products into the usual cropping systems is a promising strategy for achievemet of a high level of control of brown rot, thus contributing to the management of postharvest diseases in stone fruit in the framework of sustainable and/or organic agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Many antifungal proteins derived from Bacillus spp. have a strong inhibition activity (Gotor-Vila et al 2017). For example, the antifungal protein derived from B. subtilis ZL2-70 was shown to strongly inhibit V. dahliae, Fusariumum graminearum, C. gloeosporioides, and 19 other plant pathogens; the Bacisubin protein isolated from B. subtilis B-916 can inhibit the growth of various pathogens such as M. oryzae, B. cinerea, and A. brassicae (Luo et al 2009).…”
Section: Discussionmentioning
confidence: 99%